2002
DOI: 10.1111/j.1875-595x.2002.tb00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic prevalence of approximal enamel lesions and relationship with dentine lesions and restorations in Dutch adolescents

Abstract: The bitewing radiographs showed a considerable number of enamel lesions for these age groups. This seems to justify its use on a routine base as a diagnostic tool at the age of 14-16 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…While the findings of this study support those of other recent studies [Poorterman et al, 2002;Hopcraft and Morgan, 2005;Lillehagen et al, 2007;Chu et al, 2008] in respect of the general underestimation of carious lesions where radiographic diagnosis is not used, they build on those studies in the presentation of more detailed data on its nature and intra-oral distribution (as represented by the information in table 3 ). That the discrepancy was considerably greater for approximal surfaces than for occlusal surfaces both confirms and extends earlier findings and again underlines the need for bitewing radiographs to be a routine part of oral epidemiological surveys (and, of course, the clinical management of patients) wherever logistics and funding permit.…”
Section: Discussionsupporting
confidence: 77%
“…While the findings of this study support those of other recent studies [Poorterman et al, 2002;Hopcraft and Morgan, 2005;Lillehagen et al, 2007;Chu et al, 2008] in respect of the general underestimation of carious lesions where radiographic diagnosis is not used, they build on those studies in the presentation of more detailed data on its nature and intra-oral distribution (as represented by the information in table 3 ). That the discrepancy was considerably greater for approximal surfaces than for occlusal surfaces both confirms and extends earlier findings and again underlines the need for bitewing radiographs to be a routine part of oral epidemiological surveys (and, of course, the clinical management of patients) wherever logistics and funding permit.…”
Section: Discussionsupporting
confidence: 77%
“…Bitewing radiographs are considered useful for the detection of radiographically deep lesions that would remain undetected by clinical methods alone. A study also demonstrated the necessity of bitewing radiograph in caries detection of adolescents 13 .…”
Section: Discussionmentioning
confidence: 90%
“…Visual-tactile and radiographic examination have their limitations and are insufficient for the detection of incipient proximal lesions in many cases. Visual assessment is difficult in the interdental space and the prevalence of proximal lesions are therefore underestimated (Poorterman et al 1999;Poorterman et al 2002). Radiographs often show overlapping effects and artifacts, and their sensitivity for the detection of enamel caries is moderate (Abesi et al 2012).…”
Section: Introductionmentioning
confidence: 99%